2020
DOI: 10.1002/pssb.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Impurity Redistributions in Kesterite Absorbers

Abstract: Cu2ZnSn(S,Se)4 is a promising nontoxic earth‐abundant solar cell absorber. To optimize the thin films for solar cell device performance, postdeposition treatments at temperatures below the crystallization temperature are normally performed, which alter the surface and bulk properties. The polycrystalline thin films contain relatively high concentrations of impurities, such as sodium, oxygen and hydrogen. During the treatments, these impurities migrate and likely agglomerate at lattice defects or interfaces. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Traces of O were detected at some GBs for each of the samples investigated, which is a common finding in CIGSe and CZTS absorbers. 66,67 Oxygen contamination is argued to arise primarily through diffusion from the substrate and/or surface oxidation before deposition of a buffer layer. Preferential O segregation is reported for GBs with a specific misorientation angle, 40 but no such correlation has been established for alkali elements.…”
Section: Resultsmentioning
confidence: 99%
“…Traces of O were detected at some GBs for each of the samples investigated, which is a common finding in CIGSe and CZTS absorbers. 66,67 Oxygen contamination is argued to arise primarily through diffusion from the substrate and/or surface oxidation before deposition of a buffer layer. Preferential O segregation is reported for GBs with a specific misorientation angle, 40 but no such correlation has been established for alkali elements.…”
Section: Resultsmentioning
confidence: 99%
“…HJA can also facilitate the supplementary diffusion of alkali metals from the deep bulk to the front surface and within CdS, [ 3 ] which has been reported even at 50–200 °C. [ 38,48 ] In Figure 4e, SIMS result from the device with the combined treatments shows a distinctive Na peak within the CdS layer, in contrast to the removal of the near‐surface Na peak caused by MA‐350C, shown in Figure 1b. This rediffusion of alkali metals during HJA tends to compensate the substantial loss of Na within the junction region that occurred during MAPDA, but the concentration of Na within the junction still remains lower than that of the HJA‐Only devices, shown in Figure 4d.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that Na is able to migrate in CZTSSe via Cu vacancies at room temperature. [ 50,51 ] Thus, unless strong electrostatic interactions arise (i.e., bonding), atoms smaller than Na could show a similar behavior, allowing them to outgas or accumulate at the grain boundaries during the cooling down step, while their solubility decreases with temperature.…”
Section: Introductionmentioning
confidence: 99%